Early Diagnosis Of Heart Disease Using Alternating Decision Tree And KNN Algorithm (International Journal of Engineering and Computer Science, 2016)
The diagnosis of heart disease in most cases depends on a complex combination of clinical and pathological data. Because of this complexity, there exists a significant amount of interest among clinical professionals and researchers regarding the efficient and accurate prediction of heart disease. In case of heart disease time is very crucial to get correct diagnosis in early stage. Patient having chest pain complaint may undergo unnecessary treatment or admitted in the hospital. In most of the developing countries specialists are not widely available for the diagnosis. Hence, automated system can help to medical community to assist doctor for the accurate diagnosis well in advance. So the decision support systems play an important role in the diagnosis of heart disease. However, accurate diagnosis at an early stage followed by proper subsequent treatment can result in significant life saving.